2022
DOI: 10.3389/fnut.2022.814409
|View full text |Cite
|
Sign up to set email alerts
|

Higher Dietary Inflammatory Index Scores Are Associated With Stress and Anxiety in Dormitory-Residing Female University Students in the United Arab Emirates

Abstract: Dormitory-residing university students are at-risk of mental health problems related to unhealthy diets. The purpose of this study was to assess the association between dietary inflammatory potential and mental health of dormitory-residing female university students. This cross-sectional study was comprised of 260 undergraduate females residing in dormitories of the largest university in United Arab Emirates during Spring 2019. The Energy-adjusted Dietary Inflammatory Index (E-DIITM) scores calculated from 37 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Nine studies examined the influence of diet quality on anxiety, of which eight found significant associations. Of these studies, four used a diet quality measure and all found a negative association of diet quality with anxiety [ 46 , 49 , 64 , 65 ]. Studies using questionnaires also showed that unhealthy diet was positively associated with anxiety [ 57 , 58 , 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nine studies examined the influence of diet quality on anxiety, of which eight found significant associations. Of these studies, four used a diet quality measure and all found a negative association of diet quality with anxiety [ 46 , 49 , 64 , 65 ]. Studies using questionnaires also showed that unhealthy diet was positively associated with anxiety [ 57 , 58 , 60 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among older Irish adults at a mean age of 59, the positive association between E-DII tertiles and anxiety symptoms was significant in women as well (OR = 1.60, 95% CI = 1.15–2.24) [ 10 ]. Leveraging a 21-item Depression, Anxiety, and Stress Scale, an approximately 3-fold increased anxiety risk was observed among dormitory-residing female university students who were at the highest E-DII tertile [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Diet may directly or indirectly influence anxiety development through several mechanisms, for which chronic inflammation serves as a common substrate, such as those involved in the production and metabolism of neurotransmitters and the microbiome-gut-brain axis (MGBA) [ 7 , 8 , 9 ]. To date, with the use of the dietary inflammatory index (DII ® ), several studies have evaluated the inflammatory potential of the diet in association with anxiety symptoms, generating inconsistent findings [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. All these studies have been cross-sectional or case-control in design, limiting inferences about causality, especially when the association between diet and mental disorders is complex and likely to be bidirectional [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Work has revealed that chronic stress, low-grade chronic inflammation and body composition are interrelated and potentially affected negatively by imbalanced dietary intakes in university students [ 12 ]. Furthermore, the inadequate/imbalance diet problem often observed in college students may be more exacerbated in those living in dormitories due to practical and logistical challenges in addition to stress [ 13 , 14 ]. Other reasons contributing, not exclusively though, to nutritional problems include inadequate education and low economic status.…”
Section: Introductionmentioning
confidence: 99%